2010
DOI: 10.1007/s10549-010-0991-z
|View full text |Cite
|
Sign up to set email alerts
|

VEGF 936C>T polymorphism and breast cancer risk: evidence from 5,729 cases and 5,868 controls

Abstract: Vascular endothelial growth factor (VEGF) is one of the most potent endothelial cell mitogens and plays an important role in angiogenesis. Many published studies have evaluated the association between the VEGF 936C>T polymorphism and breast cancer risk. However, the published findings are inconsistent. In order to derive a more precise estimation of the association, a meta-analysis was performed in this study. A total of eight studies including 5,729 breast cancer cases and 5,868 controls were identified. Over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…First, we agree that the report by Pharoach et al [1] with 2,016 breast cancer cases and 2,107 controls was not included in our study. Here, we performed the meta-analysis to combine all the published data.…”
Section: Dongying Gu á Meilin Wangsupporting
confidence: 81%
See 1 more Smart Citation
“…First, we agree that the report by Pharoach et al [1] with 2,016 breast cancer cases and 2,107 controls was not included in our study. Here, we performed the meta-analysis to combine all the published data.…”
Section: Dongying Gu á Meilin Wangsupporting
confidence: 81%
“…
We have read the meta-analysis by Dongying Gu et al [1] with great interest, which was published in your journal recently. Through quantitative analysis, this meta-analysis suggested that VEGF 936C[T polymorphism might not contribute to breast cancer susceptibility.
…”
mentioning
confidence: 99%
“…A large case-control study in 500 women with breast cancer and 500 sex-and age-matched healthy control subjects found that carriers of a VEGF 936T-allele are at decreased risk for breast cancer in Austria (Krippl et al, 2003). But some meta-analyses found that the VEGF gene 936 C/T polymorphism may not contribute to breast cancer susceptibility (Gu and Wang, 2011;Qiu et al, 2011;Yang et al, 2011). A meta-analysis involving 16,703 individuals also suggested that the VEGF +936C/T, -1154A/G, -2578C/A, -634G/C and -460T/C may be not associated with risk of breast cancer development based on the currently available studies, especially for Caucasians .…”
Section: Discussionmentioning
confidence: 99%
“…The associations between three VEGF gene polymorphisms (-634 G/C, +936 C/T, and +1612 G/A) and breast cancer risk have been extensively studied, and the currently available results are inconclusive (Krippl et al, 2003;Jin et al, 2005;Lu et al, 2005;Jacobs et al, 2006;Kataoka et al, 2006;Eroglu et al, 2008;Jakubowska et al, 2008;Langsenlehner et al, 2008;Schneider et al, 2008;Wehrschuetz et al, 2009;Gu and Wang, 2011;Jin et al, 2011;Liu et al, 2011;Oliveira et al, 2011;Qiu et al, 2011;Wang et al, 2011;Yang et al, 2011;Rodrigues et al, 2012). The aim of this study was to investigate the association between three VEGF gene polymorphisms and breast cancer risk in Chinese Han patients.…”
Section: Introductionmentioning
confidence: 96%
“…However, Balasubramanian et al (2007) found that VEGF +936C was associated with decreased breast cancer risk when combined with -460T and +405C. Meta-analyses also failed to confirm the protective role of VEGF +936T (Gu and Wang, 2011;Yang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%